Highly selective determination of dopamine in the presence of ascorbic acid and serotonin at glassy carbon electrodes modified with carbon nanotubes dispersed in polyethylenimine - Rodriguez, Marcela Cecilia (2008)
We report the highly selective and sensitive voltammetric dopamine quantification in the presence of ascorbic acid and serotonin by using glassy carbon electrodes modified with a dispersion of multiwall carbon nanotubes (MWCNT) in polyethylenimine, PEI (GCE/MWCNT-PEI). The electrocatalytic activity of the MWCNT deposited on the glassy carbon electrode has allowed an important decrease in the overvoltages for the oxidation of ascorbic acid and dopamine, making possible a clear definition of dopamine, serotonin and ascorbic acid oxidation processes. The sensitivities for dopamine in the presence and absence of 1.0 mM ascorbic acid and serotonin were (2.18±0.03) × 10 5 μAM -1 (r = 0.9998); and (2.10 ± 0.07) × 10 5 μAM -1 (r = 0.9985), respectively, demonstrating the excellent performance of the GCE/MWCNT-PEI. The detection limit for dopamine in the mixture was 9.2 × 10 -7 M. The R. S. D. for the determination of 50 μM dopamine using four different electrodes was 3.9% when modified with the same MWCNT/PEI dispersion, and 4.6% when using four different dispersions. The modified electrode has been successfully applied for recovery assays of dopamine in human blood serum. Therefore, the new sensor represents an interesting and promising alternative for the electrochemical quantification of neurotransmitters and other analytes of clinical interest.